THE UTILIZATION OF JIGSAW TECHNIQUE TO IMPROVE WRITING ABILITY IN TEACHING REPORT TEXT - Kharisma Gustiningsih (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2018)
AbstractThis study was designed to improve the students’ writing ability of report text by using Jigsaw technique. This study was conducted in two cycles by following the procedures of the action research. There are planning, implementing, observing, and reflecting. Each cycle consisted of two meetings. The data of the study were gathered through the following instruments, namely observation checklist, questionnaire and test. The subjects of this study were 32 students at eleventh grade of Administrasi Perkantoran (AP) program in academic year 2016-2017 of Nurulhidayah Pasundan Vocational School. The finding of the study indicated that Jigsaw technique was effective in enhancing the students’ motivation and participation. From the result of questionnaire, it showed that 74% students participated actively in the first cycle and 80% students participated in the second cycle. This implied that the first criteria of success had been fulfilled. Furthermore, the finding of the study indicated that Jigsaw technique was successful in improving students’ writing of report text. The improvement could be seen from the increase of students’ mean writing score from 55.09 in the pre-test cycle, and 74.62 in the first cycle increase become 80.46 in the second cycle. If it calculated into class percentage, there were 4 students (12.5 %) who passed KKM in the pre-test. Meanwhile, in the cycle 1, there were 24 students (75%) who passed KKM and it gained which was in the post-test cycle 2 there were 29 students (90.62%) who passed KKM. So, it indicated that the second criteria of success has been achieved. Keywords: Jigsaw technique, writing ability, teaching report text.